2022
DOI: 10.3390/nu14132568
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Processed Food Consumption and Mental Health: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Since previous meta-analyses, which were limited only to depression and by a small number of studies available for inclusion at the time of publication, several additional studies have been published assessing the link between ultra-processed food consumption and depression as well as other mental disorders. We aimed to build on previously conducted reviews to synthesise and meta-analyse the contemporary evidence base and clarify the associations between the consumption of ultra-processed food and mental disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 84 publications
3
78
0
4
Order By: Relevance
“…A sheer number of peer-review articles have been published on the topic of ultraprocessing, embodying a general degree of consensus among independent academic researchers on the health relevance of ultra-processed food [57][58][59][60][61][62][63][64][65][66][67][68]. However, a precise definition for ultra-processed food, informing effective reformulation strategies, has yet to be achieved [26].…”
Section: Discussionmentioning
confidence: 99%
“…A sheer number of peer-review articles have been published on the topic of ultraprocessing, embodying a general degree of consensus among independent academic researchers on the health relevance of ultra-processed food [57][58][59][60][61][62][63][64][65][66][67][68]. However, a precise definition for ultra-processed food, informing effective reformulation strategies, has yet to be achieved [26].…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of ultra-processed foods, which are usually high in calories, sugar, trans fats and salt, has been connected to faster cognitive decline in later life (Weinstein et al, 2022), as well as to mood disorders (Lane et al, 2022). In contrast, a high quality diet may help to protect people from cognitive decline (Smyth et al, 2015).…”
mentioning
confidence: 99%
“…This emerging field has provided multiple lines of evidence that indicates that diet quality is an important lifestyle factor in the management and prevention of depression [65]. Meta-analyses of several prospective and cross-sectional observational studies have reported that improved diet quality is associated with a reduced risk of depression [66,67]. This association appears to be consistent across multiple datasets, throughout the lifespan, and is apparent using multiple diet quality indices [66][67][68].…”
Section: Nutritional Psychiatry and Psychologymentioning
confidence: 98%
“…Meta-analyses of several prospective and cross-sectional observational studies have reported that improved diet quality is associated with a reduced risk of depression [66,67]. This association appears to be consistent across multiple datasets, throughout the lifespan, and is apparent using multiple diet quality indices [66][67][68]. Furthermore, mechanistic studies have identified multiple pathways whereby diet may modulate depression pathophysiology with much of the recent research focusing on the role of diet in the modulation of the gut microbiota-brain axis [69,70].…”
Section: Nutritional Psychiatry and Psychologymentioning
confidence: 99%